(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The objective of this research was to develop and evaluate a learning activity package based on the concept of Active Learning to enhance creative problem-solving abilities in Chemical Equilibrium. The study aimed to gather basic information for package development, assess its efficiency, conduct experiments, and evaluate and improve the package. Results showed that the learning activity package should have an appropriate size, colorful illustrations to capture students’ attention, self-assessment features to gauge proficiency levels, and diverse content relevant to chemical equilibrium. It was recommended to include various measurement and evaluation methods to align with actual conditions. The researcher developed a set of learning activities using the 6Cs Model, comprising Challenge, Collection of Data, Cultivation, Creativity and Innovation, Comment, and Communication and Service. This package consisted of eight sets of activities, each encompassing specific components such as activity name, introduction, instructions for teachers and students, learning content and objectives, activity steps, knowledge and activity sheets, pre-tests, and post-tests. The package demonstrated an efficiency value of 81.67/82.54, meeting the 80/80 criterion. Experimental implementation of the Active Learning-based package revealed increased student engagement and enjoyment during activities. Furthermore, student learning achievements in chemistry significantly improved, indicating enhanced creative problem-solving abilities after using the package. Students’ psychological well-being and overall opinions toward the learning management with the package were also positively influenced. The research successfully developed and evaluated a learning activity package based on Active Learning principles. The package showed positive effects on student engagement, learning outcomes, problem-solving abilities, psychological well-being, and overall satisfaction.